Weed Management in Cassava in Africa: Challenges and Opportunities. (1st October 2016) - Ekeleme, Friday; Hauser, Stefan; Atser, Godwin; Dixon, Alfred; Weller, Stephen; Olorunmaiye, Patience; Usman, Hughes; Olojede, Adeyemi; Chikoye, David
Cassava (Manihot esculenta) is a major staple root crop, grown on 21 million ha in the tropics. Cassava provides calories to a large portion of the population in countries where it is grown. Cassava continues to increase in importance as a food crop and source of starch for food processing and it has been transformed from a food security crop to a cash crop, providing a source of food and income for about 500 million people in Africa, Asia and Latin America. Cassava production is concentrated in the tropical regions. Africa grows 55% of the world's cassava with Nigeria, and the Democratic Republic of Congo leading production. Southeast Asia grows 33% of the world's cassava with Thailand and Indonesia being major producers. Brazil is the major Latin American producer growing about 13% of the world supply. Africa now faces rising youth unemployment and food insecurity leading most African countries to embark on economic diversification emphasizing agriculture as a major pillar and cassava as a strategic crop in the humid zone of Sub-Saharan Africa. However, despite cassava's wide distribution, high economic and food security importance, very little research on cassava field production has been conducted. The consequence is that the current transformation of cassava from subsistence to a commercial crop is hampered by a lack of concrete, reliable and site specific recommendations on most agronomic issues. Furthermore, a crop grown on 21 million hectares worldwide has not yet attracted the interest of private industry to supply inputs, for improved plant nutrition, plant protection and weed control specifically suited to support cassava production.